Use of Modern Industrial Technologies in Architecture - Kulnazarova Zamira Bakhromovna; Makhmudova Firuza Ibraimovna (International Journal on Orange Technologies, 2022)
The article discusses the possibilities of using modern industrial technologies in the context of creating architectural objects. Using such technologies allows you to maintain the uniqueness of each object in the construction of architectural objects. The focus is on creating interesting textures and details using modern industrial technologies.